The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2337/dc06-1277
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With the Onset and Progression of Posttransplantation Diabetes in Renal Allograft Recipients

Abstract: OBJECTIVE -The aim of this study was to assess the incidence of posttransplantation diabetes mellitus (PTDM) in renal allograft recipients and to investigate factors contributing to the onset and progression of PTDM and its underlying pathogenic mechanism(s).RESEARCH DESIGN AND METHODS -A total of 77 patients with normal glucose tolerance (NGT) were enrolled in this study. An oral glucose tolerance test was performed 1 week before transplantation and repeated at 1 and 7 years after transplantation.RESULTS -The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
51
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 40 publications
(29 reference statements)
13
51
0
2
Order By: Relevance
“…The rest of the patients were assigned to the nonposttransplantation diabetic group. According to our previous study (15), cases of persistent PTDM (patients who developed diabetes within 1 year posttransplantation and remained diabetic) and late PTDM (patients who developed diabetes after 1 year posttransplantation) were assigned to the posttransplantation diabetic group. Transient PTDM cases (patients who developed diabetes within 1 year posttransplantation but eventually recovered to normoglycemia without medication) were classified as non-PTDM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the patients were assigned to the nonposttransplantation diabetic group. According to our previous study (15), cases of persistent PTDM (patients who developed diabetes within 1 year posttransplantation and remained diabetic) and late PTDM (patients who developed diabetes after 1 year posttransplantation) were assigned to the posttransplantation diabetic group. Transient PTDM cases (patients who developed diabetes within 1 year posttransplantation but eventually recovered to normoglycemia without medication) were classified as non-PTDM.…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies have reported that insulin resistance is important to the pathophysiology of PTDM, a defect in insulin secretion may also play a role in the development of PTDM (10,15). Insulin is stored in pancreatic ␤-cells as zinc-insulin crystals.…”
mentioning
confidence: 99%
“…Disturbance of insulin secretion has been suggested to be a pathophysiological event that contributes to the development of PTDM. 9,10 The role of ZnT-8 in pancreatic b-cells is also not well characterized. However, ZnT-8 is a plausible candidate factor for modification of glucose metabolism in PTDM because it was shown to colocalize with insulin vesicles in b-cells, and ablation of the gene had a negative effect on insulin secretion in animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…신장이식 환자에서도 40세 이상일 경우 이식 후 당뇨병의 발생이 증가하는 것으로 알려져 있고 [8,9], 이식 당시 나이가 60세 이상이면 젊은 사람에 비해 이식 후 당 뇨병이 2.6배 더 많이 발생한다는 보고가 있다 [10]. 또한 40세 이상의 높은 연령대는 이식 후 발생한 당뇨병이 정상 혈당으로 회복되지 않고 지속되는 중요한 고 위험 인자이 다 [11].…”
Section: 연령unclassified
“…Calcineurin억제제는 인슐린 저항성을 증가시 키는 부분도 있지만 췌장의 베타세포에 독성을 나타내어 인슐린 분비능을 저하시킴으로써 혈당을 상승시키는 부분 이 더 중요할 수 있다 [31]. 본 연구진이 7년간 추적관찰한 결과 한국인 신장이식환자에서는 인슐린 분비 결함이 인 슐린저항성의 증가보다 이식 후 당뇨병 발병에 더 중요한 다는 결과를 얻어 보고한바 있다 [11].…”
Section: 유전자unclassified